2016
DOI: 10.1136/bmjdrc-2015-000156
|View full text |Cite
|
Sign up to set email alerts
|

Association between self-stigma and self-care behaviors in patients with type 2 diabetes: a cross-sectional study

Abstract: ObjectiveGrowing qualitative evidence reveals that many patients with chronic illnesses struggle to rebuild a positive self-image after diagnosis while attempting to find a balance between their current physical status and their ongoing social duties. One factor destabilizing patients’ identities is self-stigma, which seems to affect their behavioral goals through decreased self-efficacy. We hypothesized that self-stigma would be an independent factor, distinct from self-efficacy, for developing self-care beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
3
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(91 citation statements)
references
References 41 publications
6
76
3
6
Order By: Relevance
“…Hilbert, Braehler, Haeuser, and Zenger (2014) suggested self-hate, self-blame and a feeling of inadequacy were all attributes of self-stigma. Finally, Kato, Fujimaki, Fujimori, Isogawa et al (2016) and Kato, Fujimaki, Fujimori, Izumida et al (2016) suggested that a decreased sense of self-worth, social avoidance and role conflict were key attributes.…”
Section: Predisposing Factors Results Dimensions Attributes and mentioning
confidence: 99%
See 3 more Smart Citations
“…Hilbert, Braehler, Haeuser, and Zenger (2014) suggested self-hate, self-blame and a feeling of inadequacy were all attributes of self-stigma. Finally, Kato, Fujimaki, Fujimori, Isogawa et al (2016) and Kato, Fujimaki, Fujimori, Izumida et al (2016) suggested that a decreased sense of self-worth, social avoidance and role conflict were key attributes.…”
Section: Predisposing Factors Results Dimensions Attributes and mentioning
confidence: 99%
“…However, in the current qualitative study, studies have reported the signs of stigma such as blaming or hiding one's health condition and avoiding treatment, which have been frequently appeared for both type 1 and type 2 diabetes (Browne, Ventura, Mosely, & Speight, ; Nam, Song, Park, & Song, ). Differing from patients with AIDS, individual with diabetes experience a prejudicial attitude that fosters negative attitudes towards one's self (referred to as self‐stigma; Kato, Fujimaki, Fujimori, Isogawa et al, ; Kato, Fujimaki, Fujimori, Izumida et al, ). Those with self‐stigma regarding diabetes may show unconditional obedience or, on the other hand, excessive hesitation when changing their lifestyle or accepting medical advice (Kato, Fujimaki, Fujimori, Isogawa et al, ; Kato, Fujimaki, Fujimori, Izumida et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These effects may be compounded by decreased medication adherence, poor self-care, and worsened health outcomes, all of which are associated with stigma in both HIV (I.T. Katz et al, 2013; Mahajan et al, 2008) and T2DM (Kato et al, 2016; Schabert et al, 2013). …”
Section: Discussionmentioning
confidence: 99%